Gene frequencies of HPA-1, -2 AND -3 among malay and chinese blood donors in HUSM - Azly Sumanty, Ab Ghani (2008)
Human platelet-specific antigens are found on the platelet membrane glycoproteins. These antigens are highly immunogenic and are implicated in alloimmune thrombocytopenias such as in fetal and neonatal alloimmune thrombocytopenia, post transfusion purpura and refractoriness to platelets transfusion. HP A genotyping is important because the prevalence of HP A differs among various populations. The objective of this study was to determine the HPA-1, -2 and -3 genotypes and gene frequencies in Malay and Chinese blood donors in Transfusion Medicine Unit, Hospital Universiti Sains Malaysia (HUSM). We would also like to compare the distribution ofHPA between those two ethnic groups. A cross-sectional study was done in the Transfusion Medicine Unit, HUSM from August 2006 till July 2007. Blood specimens were collected from 117 of Malay and 103 of Chinese blood donors. DNA was isolated using GENE,( ALL™ Blood SV mini kit. HPA-1, -2 and- 3 genotyping were determined by using the allele-specific oligonucleotide polymerase chain reaction (PCR-ASO) method. The results were analysed by SPSS version 12. xu The allele frequencies obtained for the Malay blood donors were 100% and 8.7% for HPA- 1a and -1b; 99.1% and 15.9% for HPA-2a and -2b; 80.7% and 78.9% for HPA-3a and -3b. For the Chinese blood donors, the results were 100% and 2.0% for HPAla and -lb; 100% and 4.9% for HPA-2a and -2b; 80.0% and 66.0% for HPA-3a and -3b. As for HPA-1 genotype results, 91.3% of the Malay blood donors were homozygous for HPA-1a/a and 8.7% were found heterozygous for HPA la/b. In the Chinese blood donors, 98.0% were homozygous for HPA-la/a and 2.0% were found heterozygous for HPA la/b. None of the samples were homozygous for HPA-lb/b. Concerning the HPA-2 genotype, 84.1% of the Malay blood donors were homozygous for HPA-2ala, 15.0% were heterozygous for HPA 2a/b and 0.9% were homozygous for HPA-2b/b. In the Chinese blood donors, 95.1% were homozygous for HPA-2a/a and 4.9% were heterozygous for HPA-2a/b. None of the Chinese blood donors were homozygous for HPA-2b/b. Regarding the HPA-3 genotype, 21.1% of the Malay blood donors were homozygous for HPA-3a/a, 59.6% were heterozygous for HPA-3a/b and 19.3% were homozygous for HPA-3b/b genotype. In the Chinese blood donors, 34.0% were homozygous for HPA-3a/a, 46.0% were heterozygous for HPA-3a/b and 20.0% were homozygous for HPA-3b/b. This study revealed the differences between the Chinese and Malay HP A genotypes. These data will be used to develop an HPA-typed platelet donor registry in our hospital. Other HP As in this system will be typed in the future,